2009
DOI: 10.3892/ijo_00000200
|View full text |Cite
|
Sign up to set email alerts
|

Mifepristone abrogates repopulation of ovarian cancer cells in between courses of cisplatin treatment

Abstract: Abstract. Repopulation of cancer cells escaping lethal chemotherapy is a critical factor hindering treatment success. One strategy to inhibit tumor cell repopulation is the use of cytostatic compounds between courses of lethal chemotherapy.In this study, we tested the hypothesis that mifepristone (MF), a steroid compound with demonstrated growth inhibition activity in ovarian cancer, should be efficacious in inducing cytostasis and preventing repopulation of ovarian cancer cells if given among rounds of cispla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 47 publications
0
15
0
Order By: Relevance
“…Following a period of 24 h allotted for cell adherence, the cells were cultured in the continuous presence of MF or DMSO for 72 h. Triplicate cultures were trypsinized, pelleted by centrifugation at 500 g for 5 min, and resuspended in the appropriate growth medium. An aliquot of each cell suspension was combined with ViaCount reagent (Guava Technologies, Hayward, CA) resulting in a 1:10 (v/v) dilution and then studied using the Guava ViaCount application in the Guava EasyCyte Mini microcapillary cytometer (Guava Technologies) as we previously described [ 15 ]. The data were acquired and analyzed using the CytoSoft 4.1 software (Guava Technologies).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Following a period of 24 h allotted for cell adherence, the cells were cultured in the continuous presence of MF or DMSO for 72 h. Triplicate cultures were trypsinized, pelleted by centrifugation at 500 g for 5 min, and resuspended in the appropriate growth medium. An aliquot of each cell suspension was combined with ViaCount reagent (Guava Technologies, Hayward, CA) resulting in a 1:10 (v/v) dilution and then studied using the Guava ViaCount application in the Guava EasyCyte Mini microcapillary cytometer (Guava Technologies) as we previously described [ 15 ]. The data were acquired and analyzed using the CytoSoft 4.1 software (Guava Technologies).…”
Section: Methodsmentioning
confidence: 99%
“…In the few existing reports that investigated the effects of MF in epithelial ovarian cancer cells, our laboratory [ 13 - 15 ] and others [ 16 , 17 ], demonstrated the efficacy of MF as a growth inhibitory agent. We have shown that MF inhibits the growth of ovarian cancer cells of different genetic backgrounds in a dose-dependent manner in vitro and in vivo [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the low toxicity of these drugs, their potential use as maintenance therapy or antirepopulation therapy following standard of care is anticipated. In this regard we have demonstrated that mifepristone was capable of abrogating the regrowth of cancer cells that escaped CDDP [ 9 ] or the combination CDDP/PTX therapy [ 10 ]. The results presented herein highlight the fact that other antiprogestins in addition to mifepristone can be efficacious against platinum/taxane double-resistant ovarian cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Following the indicated treatments, triplicate cultures were trypsinized, pelleted by centrifugation at 500 g for 5 min, and washed with PBS. The cells were resuspended in ViaCount reagent (Guava Technologies, Hayward, CA) and studied using the Guava ViaCount application in the Guava EasyCyte Mini microcapillary cytometer (Guava Technologies) as we previously reported [ 9 ]. When indicated, the concentration of drugs that caused inhibition of 50% in growth (IC50) were determined using software designed to study drug interaction, which calculates the median effective dose or Dm that is similar to the IC50 (Calcusyn, Biosoft, Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation